(Mobile Assisted Language Learning) MALL Implementation During Distance Learning - Made Erwinda Febriyanti; I Nyoman Adi Jaya Putra; Made Hery Santosa (Indonesian Journal Of Educational Research and Review, 2021)
The rules for studying from home have been implemented since the outbreak of the Corona Virus. This impacts the education sector in Indonesia, which makes the government make regulations to learn from home—in addition, making the teaching and learning process held in the context of distance learning. This study aims to analyze the learning process that applies MALL during the distance learning process and the challenges during education. The instruments used to obtain the data were self-rated questionnaires, observation checklists, and interview guidelines. This instrument was developed from the Prospective Teacher Ability Assessment Tool (APKCG) and the RASE learning design framework. The technique used to analyze the data is descriptive qualitative analysis. This study indicates that English teachers have implemented MALL during the distance learning process by using several online platforms as classrooms in their activities. Several challenges arise from teachers and students in this learning process, including the lack of teacher ability in utilizing technology, unsupported student devices, and unstable student connections.